Abscisic Acid as a Dominant Signal in Tomato During Salt Stress Predisposition to Phytophthora Root and Crown Rot - Pye, Matthew F.; Dye, Sara M.; Resende, Renata Sousa; MacDonald, James D.; Bostock, Richard M. (Frontiers in Plant Science, 2018)
Salt stress predisposes plants to Phytophthora root and crown rot in an abscisic acid (ABA)-dependent manner. We used the tomato-Phytophthora capsici interaction to examine zoospore chemoattraction and assessed expression of pathogenesis-related (PR) genes regulated by salicylic acid (SA) and jasmonic acid (JA) following a salt-stress episode. Although salt treatment enhances chemoattraction of tomato roots to zoospores, exudates from salt-stressed roots of ABA-deficient mutants, which do not display the predisposition phenotype, have a similar chemoattraction as exudates from salt-stressed, wild-type roots. This suggests that ABA action during predisposing stress enhances disease through effects on plant responses occurring after initial contact and during ingress by the pathogen. The expression of NCED1 (ABA synthesis) and TAS14 (ABA response) in roots generally corresponded to previously reported changes in root ABA levels during salt stress onset and recovery in a pattern that was not altered by infection by P. capsici. The PR genes, P4 and PI-2, hallmarks in tomato for SA and JA action, respectively, were induced in non-stressed roots during infection and strongly suppressed in infected roots exposed to salt-stress prior to inoculation. However, a tomato line deficient in SA by transgenic expression of a bacterial nahG gene did not show any compounding effects of SA deficiency relative to wild-type plants on pathogen colonization following predisposing stress. Salt stress predisposition to crown and root rot caused by P. capsici appears to be strongly conditioned by ABA-driven mechanisms in tomato, with the stress compromising SA- and JA-mediated defenses to contribute to the increased susceptibility.